Kepemimpinan Digital dalam Manajemen ASN di Kabupaten Bogor - Rusliandy Rusliandy (Universitas 17 Agustus 1945, 2024)
The research will focus on analyzing digital leadership in the digitalization of ASN management in Bogor Regency that has already been established and implemented. The research will utilize a qualitative approach, employing data collection techniques such as interviews, observations, and literature studies. The validation process will involve data and source triangulation. The study's findings indicate that although the digitalization of ASN management has been carried out, there are still weaknesses present. These weaknesses include a fragmented and non-integrated system. Additionally, digital leadership currently faces challenges such as a digital divide, low commitment, poor adaptation to digital culture, inadequate regulations that do not fully cover the various systems being developed, and weak information system security. The research recommends that the Bogor Regency government prioritize the identification of a digital leadership figure who meets specific criteria. These criteria include possessing a vision and mission for digital transformation, demonstrating digital competence, collaboration skills, the ability to formulate regulations, fostering a digital culture, and exhibiting strong commitment and leadership abilities.